Therapeutic options for CTLA-4 insufficiency - Egg, David; Rump, Ina Caroline; Mitsuiki, Noriko; Rojas-Restrepo, Jessica; Maccari, Maria-Elena; Schwab, Charlotte; Gabrysch, Annemarie; Warnatz, Klaus; Goldacker, Sigune; Patiño, Virginia; Wolff, Daniel; Okada, Satoshi; et al. (Journal of allergy and clinical immunology, 2022)
BACKGROUND: Heterozygous germline mutations in cytotoxic T lymphocyte-associated antigen-4 (CTLA4) impair the immunomodulatory function of regulatory T cells. Affected individuals are prone to life-threatening autoimmune and lymphoproliferative complications. A number of therapeutic options are currently being used with variable effectiveness. OBJECTIVE: Our aim was to characterize the responsiveness of patients with CTLA-4 insufficiency to specific therapies and provide recommendations for the diagnostic workup and therapy at an organ-specific level. METHODS: Clinical features, laboratory findings, and response to treatment were reviewed retrospectively in an international cohort of 173 carriers of CTLA4 mutation. Patients were followed between 2014 and 2020 for a total of 2624 months from diagnosis. Clinical manifestations were grouped on the basis of organ-specific involvement. Medication use and response were recorded and evaluated. RESULTS: Among the 173 CTLA4 mutation carriers, 123 (71%) had been treated for immune complications. Abatacept, rituximab, sirolimus, and corticosteroids ameliorated disease severity, especially in cases of cytopenias and lymphocytic organ infiltration of the gut, lungs, and central nervous system. Immunoglobulin replacement was effective in prevention of infection. Only 4 of 16 patients (25%) with cytopenia who underwent splenectomy had a sustained clinical response. Cure was achieved with stem cell transplantation in 13 of 18 patients (72%). As a result of the aforementioned methods, organ-specific treatment pathways were developed. CONCLUSION: Systemic immunosuppressants and abatacept may provide partial control but require ongoing administration. Allogeneic hematopoietic stem cell transplantation offers a possible cure for patients with CTLA-4 insufficiency.
Keywords: zárodečné mutace; dospělí; Germ-Line Mutation; Female; Infant; dítě; předškolní dítě; intersticiální plicní nemoci; Adult; Autoimmune Diseases; ženské pohlaví; mladý dospělý; syndromy imunologické nedostatečnosti; Adolescent; antigen CTLA-4; CTLA-4 Antigen; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; agamaglobulinemie; autoimunitní nemoci; genetické asociační studie; Immunologic Deficiency Syndromes; Male; kojenec; Aged; Lung Diseases, Interstitial; Child, Preschool; Young Adult; Agammaglobulinemia; Transplantation, Homologous; lidé středního věku; Child; senioři; mužské pohlaví; Middle Aged; mladiství; Genetic Association Studies; Humans